The challenges of supporting necessity entrepreneurs: Understanding loan officer exit in microfinance - Doering, Laura; Wry, Tyler (Journal of Business Venturing, 2022)
Necessity entrepreneurship can serve as a pathway out of poverty for low-income individuals, with microfinance often providing important financial support. Yet the relational lending strategies common among microfinance institutions may influence loan officer turnover and, in turn, compromise entrepreneurs' access to credit. While there is some reason to suspect that relational lending with poor entrepreneurs will increase retention, we propose that serving the poor may make loan officers more likely to quit: loan officers in commercial microfinance institutions are unlikely to have strong commitments to poverty alleviation and may be taxed by the challenging fieldwork associated with lending in poor areas. Qualitative and quantitative data from a microfinance bank in Latin America support our expectations, showing that exit becomes more likely when loan officers' work involves more poor clients and that the effect is strongest when such work demands intensive fieldwork in low-income areas. Supplementary analyses of trends across the global microfinance industry demonstrate that poor clients have a stronger impact on exit in for-profits than non-profits, suggesting that prosocial motives among non-profit employees may have a buffering effect. Overall, our study reveals how providing services to necessity entrepreneurs can have negative, unexpected consequences for frontline employees.